Community Empowerment Analysis Regarding Environmental Sanitation in Flood-Prone Areas - R. Firwandri Marza; Basuki Arioseno; Kamal Kasra (POLTEKKES KEMENKES PADANG, 2023)
A disaster situation is an event or event that has the potential to cause damage to environmental facilities and infrastructure, such as the provision of clean water and sanitation conditions. Diseases that have the potential to occur in such conditions are diarrheal diseases and infectious diseases that are transmitted through the 'fecal-oral route'. The purpose of this research is the analysis of community empowerment regarding environmental sanitation in flood-prone areas in Jorong Aia Taganang, Galanggang Tangah, Kenagarian Salayo, Solok Regency. The research was carried out with a qualitative approach, with a descriptive approach. , with in-depth interviews (in-depth interview) Research results in Almost all respondents said that environmental health problems are important to be available, but some say, clean water is necessary to clean, while disposal of feces is a problem, just defecate in heavy water, carry on defecating it. Meanwhile, trash is washed away when the flood comes. Suggestions are requested for the Solok Regency Government to socialize the importance of Sanitation during a Disaster. The follow-up of this research is in the form of community service regarding Community Empowerment regarding improving the quality of clean water and environmental sanitation.